Influence of board characteristics on risk disclosure quality in China's growth enterprise market companies - Huang, Yanyu (2017)
Risk disclosure has become a popular research topic in the field of theory and practice. However, there are few empirical studies on the risk disclosure of Chinese listed companies. Factors influencing Chinese companies’ risk disclosure quality have not been sufficiently researched and verified. So, building upon previous studies, the present study explores the relation between board characteristics and the quality of risk disclosure in China.